Um modelo baseado em agentes para o ciclo de vida dos insetos : aplicação na interação afídeo-planta-vírus - Toebe, Josué (2014)
This study aimed to propose a model for the simulation of populational dynamics of insect agricultural pests. This model was built using the agent-based modeling (ABM) and implemented in the shape of a framework. For this, the model considered the different aspects and specificities of the insect life cycle, such as reproduction, movement, mortality, nutrition and development. The evaluation of the model was performed with the parameterization and calibration of it for aphid Rhopalosiphum padi L. (Hemiptera: Aphididae) in two wheat cultivars - Embrapa 16 and BRS Timbaúva. The evaluation was performed considering semi-controlled environmental and field conditions, of the region of Passo Fundo - RS. Furthermore, the model was extended and coupled to a simulation model of development of plants, for the purpose of providing a simulation of viral dispersion and its effect on the plants. A case study was conducted and simulation scenarios were set up to evaluate the effectiveness of the method in the simulation of the dispersion of viral complex causer of the yellow disease in the barley in wheat by aphid vector Rhopalosiphum padi. The simulation method used was successful for the case study, propitiating the estimation of damage to the plants